Penghijauan Lingkungan: Strategi Partisipatif untuk Mengoptimalkan Penanaman Tumbuhan - Vicky Yoga Satria; Hendrianto Udjari; Jahroni Jahroni; Arif Rachman Putra; Didit Darmawan; Rio Saputra; Samsul Arifin; Rommy Hardyansah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This community service research aims to describe the activities of planting plant varieties to support efforts to green the neighborhood area around RT 1 RW 4 Dukuh Menanggal. The author and the research subjects try to try to reforest the area with plant varieties that are suitable for urban areas in Dukuh Menanggal. This community service research uses descriptive qualitative research with observation and documentation data collection techniques and data analysis using data collection, data presentation, data condensation and data conclusion. The research method used in community service is Participatory Action Research (PAR). The results showed that plant varieties were able to optimally green the neighborhood area of RT 1 RW 4 Dukuh Menanggal.